2015
DOI: 10.1002/jssc.201500917
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative analysis of adulterant Lonicera species in preparations of Lonicerae Japonicae Flos

Abstract: Lonicerae Japonicae Flos is often adulterated with Lonicerae Flos, which is derived from the other four Lonicera species, in both the crude drug and Lonicerae Japonicae Flos preparations. We proposed a methodology for the quantitative analysis of adulterant Lonicerae Flos in Lonicerae Japonicae Flos preparations. Taking macranthoidins A, B, dipsacoside B (saponins), sweroside (iridoids), and luteolin-7-O-d-glucoside (flavonoids) as markers, a method of ultra high performance liquid chromatography with triple q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Centauroside (146) and (E)-aldosecologanin (185) exhibited much more potent NO inhibitory activities than the positive control minocycline in vitro (IC 50-= 20.07 ± 0.37 lM), with IC 50 values of 7.96 ± 0.47 and 12.60 ± 1.50 lM, respectively. Zhang et al (2015) tr trace, nd not detect, nr no record What's more, neither of them showed significant cytotoxicity at the concentration of 100 lM . In this literature, it also mentioned that secoiridoid glycosides had a more positive effect on a-glucosidase inhibition than other iridoid glycosides, while the presence of a methoxy group at C-7 or a double bond at C-6 or C-7 appeared to reduce the inhibition markedly.…”
Section: Iridoidsmentioning
confidence: 94%
See 1 more Smart Citation
“…Centauroside (146) and (E)-aldosecologanin (185) exhibited much more potent NO inhibitory activities than the positive control minocycline in vitro (IC 50-= 20.07 ± 0.37 lM), with IC 50 values of 7.96 ± 0.47 and 12.60 ± 1.50 lM, respectively. Zhang et al (2015) tr trace, nd not detect, nr no record What's more, neither of them showed significant cytotoxicity at the concentration of 100 lM . In this literature, it also mentioned that secoiridoid glycosides had a more positive effect on a-glucosidase inhibition than other iridoid glycosides, while the presence of a methoxy group at C-7 or a double bond at C-6 or C-7 appeared to reduce the inhibition markedly.…”
Section: Iridoidsmentioning
confidence: 94%
“…A large number of studies indicate that saponins contented in JYH are fewer than those in SYH Chai et al 2005;Zhang et al 2015;Yang et al 2016). Saponins are the most compounds in SYH (Fig.…”
Section: Saponinsmentioning
confidence: 99%
“…L. fulvotomentosa ) , L. confusa, L. hypoglauca , and L. macranthoides . Lonicerae Flos is much cheaper than Lonicerae japonicae Flos 14 . According to the theory of traditional Chinese medicine characteristics, Eucommiae Folium and Lonicerae japonicae Flos have totally different pharmacology, so the two herbal materials should be clearly distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…They are typical Chinese medicines of "heterologous effect". Numerous literature has reported that LF has similar pharmacological activities as LJF, 8,11 only with a marginal difference in the strength of the drug effect. But until now, there is still no recognised theory to explain this phenomenon.…”
Section: Introductionmentioning
confidence: 97%